Awareness and attitudes of local people toward wildlife conservation in the Rungwa Game Reserve in Central Tanzania. Issue 6 (2nd November 2018) - Hariohay, Kwaslema Malle; Fyumagwa, Robert D.; Kideghesho, Jafari R.; Røskaft, Eivin
ABSTRACT: Studies have demonstrated that wildlife conservation success depends on local people's attitudes toward wildlife. We conducted semi-structured interviews with 240 respondents living in five villages outside the south-western Rungwa Game Reserve (RGR). Results revealed 89% of the respondents were aware of wildlife conservation, and their awareness varied with age, education, immigration status, and distance to the protected area (PA). Factors influencing the attitude of local people toward wildlife in the area included age, distance to the PA, education level, and sources of income. Depredation and crop damage negatively influenced people's attitudes toward problem animals. For effective conservation, the attitudes of local people toward wildlife need to be considered. This conservation will be achieved through timely compensation schemes, the involvement of the local people in conservation planning, and the provision of education programs about sustainable conservation.